Knowledge and Risk Perceptions of Occupational Infections Among Health-care Workers in Malaysia - Ganesh Chidambar Subramanian; Masita Arip; T.S. Saraswathy Subramaniam (Elsevier, 2017)
Health-care workers are at risk of exposure to occupational infections with subsequent risk of contracting diseases, disability, and even death. A systematic collection of occupational disease data is useful for monitoring current trends in work situations and disease exposures; however, these data are usually limited due to under-reporting. The objective of this study was to review literature related to knowledge, risk perceptions, and practices regarding occupational exposures to infectious diseases in Malaysian health-care settings, in particular regarding blood-borne infections, universal precautions, use of personal protective equipment, and clinical waste management. The data are useful for determining improvements in knowledge and risk perceptions among health-care workers with developments of health policies and essential interventions for prevention and control of occupational diseases.